VVITA Erasmus+ C6-C7 The Opening Conference - Marius Voica; Elena Cristina Mandrescu; Mihaela Harmanescu; Andra Panait; Adrian Moleavin; Marina Mihaila (Urbanism. Arhitectura. Constructii, 2019)
The present paper is the dedicated review of the Opening Conference of C6-C7 activities within VVITA Erasmus+ project (Intensive programmes for higher education learners: “Romanian applied study on rural heritage sustainable revitalization methodology approaching inter-,multi- and trans- disciplinarily of build culture aiming to promote social inclusion for disadvantage and remote communities”, Sfistofca and Tulcea, Romania, 18-27th May 2019; 18th May 2019, “Ion Mincu” University of Architecture and Urbanism (UAUIM), Council Hall, Bucharest, Romania), and specific entitled Intensive programmes for higher education learners: “Romanian applied study on rural heritage sustainable revitalization methodology approaching inter-, multi- and trans- disciplinarily of build culture aiming to promote social inclusion for disadvantage and remote communities.”